Design and efficient implementation of a chaos-based stream cipher - Abutaha, Mohammed; Assad, Safwan El; Queudet, Audrey; Deforges, Olivier (Inderscience Publishers (IEL), 2017)
We designed and implemented a stream cipher cryptosystem based on an efficient chaotic generator of finite computing precision (N = 32). The proposed structure of the chaotic generator is formed by a Key-setup, an IVsetup, a non-volatile memory, an output and an internal state function. The cryptographic complexity mainly lies in the internal state containing two recursive filters, with one, two or three delays. Each recursive filter includes a perturbation technique using a linear feedback shift register. The first recursive filter includes a discrete skew tent map, and the second one includes a discrete piecewise linear chaotic map. The chaotic generator is implemented in sequential and parallel versions using Pthread library in a secure manner. The proposed Stream ciphers have very good performance in terms of security and execution time. Experimental results highlight the robustness of the proposed system against known cryptographic and statistical attacks